An Ethical Application to Student-Athlete Name, Image, and Likeness (NIL) Sponsorship - John Fortunato (Journal of Intercollegiate Sport)
Student-athletes receiving the ability to profit off of their name, image, and likeness (NIL) ignited an industry disruption in college sports.  Brands using student-athletes for sponsorship became a main NIL activity.  Student-athletes are attractive to brands because of their social media following and their authentic connection with fans, alumni, and youths in the community.  Sponsors having a greater presence in college sports as a result of NIL raises ethical concerns on issues of student-athlete recruiting, potential negative brand associations for a university, and sponsorship revenue being diverted from a university and going to a select few student-athletes which could result in the elimination of some university sports teams.  The study of business ethics is advanced by examining various industries, each with its unique variables.  This article analyzes student-athlete NIL sponsorship activities by applying The Principles and Practices for Advertising Ethics provided by the Institute for Advertising Ethics.  It is important to study ethics in the context of NIL because its marketing and regulatory implementation are still in their infancy.  This timely ethical evaluation of NIL activities draws upon the literature that describes sponsorship principles, characteristics and motivations of sports fans, the economic and marketing systems of college sports, and an ethical standard.  Understanding and applying these concepts can lead to more effective decision-making and better outcomes for student-athletes, universities, sponsors, and consumers.  Adopting an ethical approach can inspire trust in the practice of brands using student-athletes for sponsorships.